(untitled) (Annals of Medical Research, 2022)
Aim: To research the perioperative significance of the simple laboratory test values on differentiating complicated acute appendicitis. Materials and Methods: The medical records of 216 acute appendicitis patients were examined retrospectively. Patients were divided into two groups according to pathological results (non-complicated (n=157) and complicated (n=59)). The demographic and clinical data, laboratory findings, length of hospital stay, and pathological results were compared between the two groups. Receiver operating characteristics (ROC) curves were performed to analyze the optimal cutoff value of numerical variables which were significantly differed between the group comparisons. Results: The preoperative data were similar in two groups except for age. The length of hospital stay (LOHS) was longer and total/direct bilirubin levels higher in the complicated group (p=0.002, p=0.002, and p=0.002, respectively. The lymphocyte level and amylase level were lower in the complicated group (p=0.02 and p=0.004, respectively). ROC curve analysis showed a cutoff values as follows: total bilirubin ≥0.89 mg/dL, direct bilirubin ≥0.43 mg/dL, lymphocyte ≤1.63%, and amylase ≤46.5 U/L. Conclusion: Preoperative higher total and direct bilirubin levels are able to predict complicated appendicitis. Preoperative higher serum amylase levels should not have a place in the differential diagnosis of complicated appendicitis. This means that if serum amylase is elevated in a patient with doubted acute appendicitis, it does not suggest acute complicated appendicitis